Interactive Multimedia Gamification-Based Physical Fitness Activities In Nearpod Platform - Gustiawati, Resty; Surya, Terbit Surya; Ega Trisna Rahayu (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2025)
The ever-evolving digital era, the use of multimedia technology in education is essential in learning, including in physical education. The urgency of this study is that physical education in Indonesia is currently facing an emergency situation due to the lack of efficiency in learning in schools and the lack of understanding of the importance of introducing physical education with the help of technology supported by the observation of researchers on PJOK teachers in Karawang Regency with different teaching places resulting in the use of this website-based learning technology is very lacking. And the students faced are nativ generation students who have understood technology media since childhood. The purpose of the study is to develop a gamification-based interactive multimedia on the Nearpod platform to increase individual engagement and motivation in physical fitness activities. In addition, this study also aims to evaluate the effectiveness of the platform in improving user participation and physical fitness outcomes. This research uses the R&D (Research & Development) method with the ASSURE development stage. The ASSURE stage consists of six stages, namely: Analyze Learners, States Objectives, Select Methods, Media, and Material, Utilize Media and Materials, Evaluate and Revise, This research involves 4 validators, namely material, media, digitization and engineering experts and 40 grade IX students of SMP 1 Tempuran Karawang RegencyBased on the results of research and development of interactive multimedia physical fitness activities obtained validation results by media experts, materials, and digitization showed results of 81%, 83%, and 83%, respectively, which were classified as valid but required revision. This multimedia was piloted on students and received a "very decent" response with an average score of 83%, indicating its appeal and usefulness